2022
DOI: 10.3390/ijerph191710509
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Oral Lesions Associated with Tobacco Smoking, E-Cigarette Use and COVID-19 Infection among Adolescents and Young People in Nigeria

Abstract: COVID-19 infection is associated with oral lesions which may be exacerbated by tobacco smoking or e-cigarette use. This study assessed the oral lesions associated with the use of e-cigarettes, tobacco smoking, and COVID-19 among adolescents and young people in Nigeria. A national survey recruited 11–23-year-old participants from the 36 States of Nigeria and the Federal Capital Territory, Abuja. Data were collected using Survey Monkey®. Binary logistic regression analysis was conducted. Statistical significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Among the remaining five papers, two 54,62 collected data from Lagos, one 67 collected data from Lagos and Abuja, and two 59,61 collected data from all 36 states in Nigeria including the Federal Capital Territory (Table 1).…”
Section: Study Locationmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the remaining five papers, two 54,62 collected data from Lagos, one 67 collected data from Lagos and Abuja, and two 59,61 collected data from all 36 states in Nigeria including the Federal Capital Territory (Table 1).…”
Section: Study Locationmentioning
confidence: 99%
“…Three papers provided evidence of the prevalence of e-cigarette use in Nigeria, and all three studies surveyed a combined population of adolescents and young adults. 54,59,61 All three papers reported different lifetime prevalence rates which ranged from 5.8% to 19.8%.…”
Section: Prevalence Of E-cigarette Use In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…A narrative review concluded that COVID-19 patients had a higher prevalence of oral manifestations compared to healthy controls [ 25 ]. A separate Nigerian study [ 26 ] found that COVID-19 patients had a higher prevalence of oral complications such as dry mouth, taste disturbances, and oral ulcers than healthy controls.…”
Section: Oral Consequences Of Covid-19mentioning
confidence: 99%
“…This can lead to uncertainty and conflict in decision-making about personal and family safety, as well as economic problems that may linger from the pandemic (Zafri et al, 2021b). COVID-19 has affected the mental health of people in Nigeria and how this situation is different from the ongoing "new normal" (Alade et al, 2022). Mental health is a very important issue for the people of Nigeria during the pandemic and the new normal (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%